2021
DOI: 10.1088/1361-6579/ac05d4
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive threshold split Bregman algorithm based on magnetic induction tomography for brain injury monitoring imaging

Abstract: Objective. Traditional magnetic induction tomography (MIT) algorithms have problems in reconstruction, such as large area error (AE), blurred boundaries of reconstructed targets, and considerable image noise (IN). As the size and boundary of a lesion greatly affect the treatment plan, more accurate algorithms are necessary to meet clinical needs. Approach. In this study, adaptive threshold split Bregman (ATSB) is proposed for brain injury monitoring imaging in MIT. We established a 3D brain MIT simulation mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 35 publications
(30 reference statements)
1
5
0
Order By: Relevance
“…MIT was used for monitoring. This previous study showed that MIT can image and identify the location of intracranial injury after TBI (Zhang et al 2021). In the present study, the intracranial pressure increased following craniocerebral injury in rabbits, initiating compensatory mechanisms.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…MIT was used for monitoring. This previous study showed that MIT can image and identify the location of intracranial injury after TBI (Zhang et al 2021). In the present study, the intracranial pressure increased following craniocerebral injury in rabbits, initiating compensatory mechanisms.…”
Section: Discussionsupporting
confidence: 59%
“…In theory, it will achieve better imaging results than those obtained using experimental animals. Although the human spinal uid layer will be thicker, previous simulation studies performed by our group show that better imaging can be performed even in the presence of cerebro-spinal uid (Zhang et al, 2021). The imaging in this study is based on twodimensional imaging, which mainly re ects the changes in electrical conductivity of the plane where the coil is located.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have applied the split Bregman iterative algorithm to solve a similar problem but with the gradient penalty in [17] . Recently, split-Bregman algorithm has attracted a lot of attention in various image processing applications [20] , [26] , [29] .…”
Section: Nonlinear Formmentioning
confidence: 99%